Homonymy in "It Ends with Us" Novel by Colleen Hoover - Aulia, Winda; Sihaan, Irham Aliyafi; Damanik, Emeliya Sukma D; Reynanda, Lutfi; Astari, Rina (e-Journal of Linguistics, 2022)
This study aims to analyze homonymy found in colleen hoover's novel it ends with us. the method that used in this study is qualitative research, which is the writer investigate phenomena in the natural contexts, attempting to make sense of or interpret phenomena in terms of the meanings that people assign to them. the data was taken from the source of data, which is from colleen hoover's novel, it ends with us. the result of this study is the writers found that there are 3 types homonyms, which is consist of 2 pairs of absolute homonym, 2 pairs of homograph, and 3 pairs of homophone in colleen hoover's novel it ends with us, and the dominant types of homonymy in colleen hoover's novel "it ends with us" is homograph.